O pensar e o fazer de alfabetizadoras participantes da proposta do SIGA em Mato Grosso - Santana, Maurecilde Lemes da Silva (2013)
In this study aims to understand how teachers conceive of literacy teachers public schools the process of literacy and literacy and develops their teaching actions as participants in the proposal of SIGA-Integrated Learning Management System, in Mato Grosso. The proposal was implemented by SEDUC, in 2010, in some schools from state schools net and in 2011, extended to all urban and country schools that meet the first cycle. The theoretical- methodological assumptions ensure to literacy and the literacy while inseparable processes and the development of capabilities that enable children to articulate their experiences and knowledge for the resolution of everyday problems. In this way, it is hoped that the children are literate until the eight year old seizing the writing system and its different forms of interpreting, read and insert in the socio-cultural living space with the various manifestations of writing and participating in social practices that it involve. I had adapted as benchmark of analysis to Languages Area of knowledge in a social constructivism theory aspect, considering the structuring axes and the development work of the specific capabilities of each axis. The axes correspond the Understanding and appreciation of written culture, Orality, Production of reading and Production of writing, being essential to address the children's literature and its essentiality in the formation of the reader, for which I sought thematic authors who ensure the fundamentals of the study. As research methodology, I opted for qualitative research, considering the alternative to insertion in locus and the interaction with the object of study in their natural environment for data collection. The instruments used were the observation, questionnaire, interview recorded with semi-structured questions screenplay and documentary analysis. The diary work of teachers is configured by the work involving discursive genres, diversified production strategies of reading and writing, including the children's literature, dialogic and interactive relationship with students, literacy development situations, at the same time that is marked by the need of training, inconsequence of not having clarity of epistemological assumptions, difficult to operate the system, emphasis on education because of repetitive activities proposals for the acquisition of writing. The collective work is essential to the proposal make it work and the most important thing is that they are willing to reflect on what place it works in the project in order to improve the quality of reading and writing practices and development of orality, precondition for coexistence and participation in society.